2021
DOI: 10.33545/comed.2021.v4.i3a.198
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, attitude and practices toward elderly depression among primary health care physicians, Riyadh, Saudi Arabia, 2021.

Abstract: Background: Elderly people need to care services in particular to maintain a high quality of life and health status. Managing the health needs of geriatric patients is part of the continuity of care family physicians provide to their patients. Aims: to assess physicians' attitude, perception and practice toward depression in elderly in primary care sitting. Methodology: A cross-sectional study to assess primary health care physicians' attitude and perceptions and practices toward depression in elderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Moreover, the CDC indicated that depression rates among the elderly with chronic conditions and those with reduced capabilities are higher than in the general population, which might exacerbate the situation by reducing quality of life, increasing healthcare costs, utilizing critical healthcare resources, increasing mortality, and doubling the rate of suicide compared to the general population [ 7 ]. Studies show that the incidence of depression among the elderly is much higher in Arab countries, with 24.3% in Jordan, 16.9% in Oman, 38.9% in Iraq, 38.7% in Egypt, 25% in Kuwait, and 17.5% in Saudi Arabia [ 9 ]. This is due to the misdiagnosis of geriatric depression and a lack of community knowledge about the importance of early depression screening to improve therapeutic outcomes and quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the CDC indicated that depression rates among the elderly with chronic conditions and those with reduced capabilities are higher than in the general population, which might exacerbate the situation by reducing quality of life, increasing healthcare costs, utilizing critical healthcare resources, increasing mortality, and doubling the rate of suicide compared to the general population [ 7 ]. Studies show that the incidence of depression among the elderly is much higher in Arab countries, with 24.3% in Jordan, 16.9% in Oman, 38.9% in Iraq, 38.7% in Egypt, 25% in Kuwait, and 17.5% in Saudi Arabia [ 9 ]. This is due to the misdiagnosis of geriatric depression and a lack of community knowledge about the importance of early depression screening to improve therapeutic outcomes and quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the incidence of depression among the elderly is much higher in Arab countries, with 24.3% in Jordan, 16.9% in Oman, 38.9% in Iraq, 38.7% in Egypt, 25% in Kuwait, and 17.5% in Saudi Arabia [ 9 ]. This is due to the misdiagnosis of geriatric depression and a lack of community knowledge about the importance of early depression screening to improve therapeutic outcomes and quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%